TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PELAKU PENGANIAYAAN YANG MENGAKIBATKAN LUKA BERAT DIBAGIAN KEPALA (PUTUSAN NOMOR : 317/PID.B/2018/PN.MDN) - David Seh Tumonggi Sialagan (jurnal.unprimdn.ac.id, 2019)
Criminal acts of torture are acts carried out in the form of attacks on the bodyor parts of the body that cause pain or injury, and even cause death. On this occasion,this paper aims to find out the application of criminal law to criminal acts of abusethat result in severe headaches. And to find out the legal considerations for judges inthe imposition of criminal acts against perpetrators of criminal acts of abuse whichresulted in serious injuries in the head in the case decision number 317 / PID.B / 2018/ PN MEDAN. To achieve these objectives the author uses data collection techniqueswith a literature study and the type of research carried out is normative juridical. Theresults of this study indicate the application of the law decided by the judge to the crimeof abuse which resulted in severe head injuries. And the legal considerations of judgesin imposing criminal sanctions must first be fulfilled elements of the article in theindictment and actions of judges to consider matters that alleviate and burden thedefendants (perpetrators of the persecution).